220 Effects of supplemental leucine in milk replacer on lamb growth performance and carcass characteristics. (30th November 2020) - Reiners, Jessica N; Anderson, Steven; Hoffman, Travis; Swanson, Kendall C
Abstract: Twenty-four fall born Dorset-cross twin or triplet ram lambs were used to determine effects of supplemental leucine in milk replacer fed to neonatal lambs on pre- and post-weaning growth, organ weight, and carcass performance. Lambs were weighed after birth and allowed to nurse on dams for 12 h to allow for colostrum intake. At 12 h post-birth, lambs were assigned to one of two treatments: milk replacer (CON) and milk replacer with leucine added at 3% as-fed (LEU). Milk replacer treatments were offered for ad libitum intake for 42 d through a Lac-Tek milk machine. After 42 d, lambs were weaned and adapted to a finishing diet. Lambs were maintained on a finishing diet until one of two slaughter dates. Lamb weight through the pre- and post-weaning phases, organ weights, and carcass traits were determined. Data were analyzed using the GLM procedure of SAS. Leucine supplementation increased lamb ADG (P = 0.007) in the pre-weaning period. Leucine supplementation did not affect final body weight or ADG for the finishing period. Weight of the rumen tended to increase in LEU lambs (P = 0.09). Carcass weight and backfat were not affected by leucine supplementation. Body wall fat thickness was greater (P = 0.05) in lambs supplemented with leucine. Ribeye area, yield grade, leg scores, and percent of boneless, closely trimmed retail cuts were not affected by leucine supplementation. Neonatal growth in the pre-weaning period was enhanced, but long-term growth and muscle development were not affected by leucine supplementation.